Serious Fun: Gaming the Book Festival - Driscoll, Beth; Squires, Claire (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2018)
The book festival provides an intriguing instance of the overlapping cultural, social and economic dimensions of contemporary literary culture. This article proposes the application of a new conceptual framework, that of game-inspired thinking, to the study of book festivals. Game-inspired thinking uses games as metaphors that concentrate and exaggerate aspects of cultural phenomena in order to produce new knowledge about their operations. It is also an arts-informed methodology that offers a mid-level perspective between empirical case studies and abstract models. As a method, our Bookfestivalopoly and other games focus attention on the material, social and ideological dimensions of book festivals. In particular, they confirm the presence of neoliberal pressures and neocolonial inequalities in the “world republic of letters.” Our research thus makes a contribution to knowledge about the role of festivals within contemporary literary culture, and provides a model for researchers of cultural phenomena who may want to adopt game-inspired, arts-informed thinking as an alternative to traditional disciplinary methods.